2005
DOI: 10.1373/clinchem.2004.046292
|View full text |Cite
|
Sign up to set email alerts
|

Future Biomarkers for Detection of Ischemia and Risk Stratification in Acute Coronary Syndrome

Abstract: Background: Evaluation of patients who present to the hospital with a complaint of chest pain or other signs or symptoms suggestive of acute coronary syndrome (ACS) is time-consuming, expensive, and problematic. Recent investigations have indicated that increases in biomarkers upstream from biomarkers of necrosis (cardiac troponins I and T), such as inflammatory cytokines, cellular adhesion molecules, acute-phase reactants, plaque destabilization and rupture biomarkers, biomarkers of ischemia, and biomarkers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
269
0
31

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(307 citation statements)
references
References 108 publications
7
269
0
31
Order By: Relevance
“…However, we think the index may be efficient only for the monitoring of patients with known baseline IMA and albumin concentrations. Lippi et al 11,14 IMA values may be affected by albumin concentrations also within reference limits. In the present study, IMA elevation after PCI reflects, at least in part, decreased albumin concentrations in patients with mild ischaemia during PCI.…”
Section: Discussionmentioning
confidence: 97%
“…However, we think the index may be efficient only for the monitoring of patients with known baseline IMA and albumin concentrations. Lippi et al 11,14 IMA values may be affected by albumin concentrations also within reference limits. In the present study, IMA elevation after PCI reflects, at least in part, decreased albumin concentrations in patients with mild ischaemia during PCI.…”
Section: Discussionmentioning
confidence: 97%
“…18 The significance of this assay in determining periods of ischemia is evident in that it has recently been licensed by the U.S. Food and Drug Administration as a rule-out test for cardiac ischemia. 25 Though the presence of IMA is not diagnostic of a cardiac infarct, as any regional ischemia has the potential to generate IMA, its absence indicates that it is most unlikely and patients with a low IMA score can be discharged. The loss of metal chelation function, as evidenced by increasing IMA, would contribute to an environment of continued oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…12 In support of this idea, recent studies have shown that the circulating levels of MMP-9 may be used as a bloodborne biochemical marker for cardiovascular diseases. 12,[14][15][16] Furthermore, MMP-9 plasma levels predicted mortality in patients with coronary artery disease. 12 Together, these findings suggest that plasma MMP-9 and MMP-2 may have diagnostic and prognostic value.…”
Section: Introductionmentioning
confidence: 99%